Do Non-Reflective Thinkers Apply Extreme Personal Meanings to their Activated Moods?. Issue 5 (26th April 2017) - Dodd, Alyson L.; Haigh, Matthew
Abstract : Background : The integrative cognitive model of mood swings proposes that mood symptoms are driven by extreme, self-referent appraisals. For example, if activated mood is appraised positively, this prompts selection of mood regulation strategies that act to up-regulate mood. Appraisals are driven by fast and automatic Type 1 cognitive processes, which, left unchecked, can cause activated mood to escalate.Aims : It was hypothesized that greater propensity to override these automatic processes by engaging in reflective (Type 2) thinking would be negatively associated with extreme appraisals of activation and activation.Method: Study 1 ( n = 150) was a cross-sectional survey consisting of measures of activation, extreme appraisals, and an objective performance-based measure of the propensity to engage in reflective thought (cognitive reflection test; CRT). In Study 2 ( n = 241) participants completed these measures plus three alternative measures of effortful cognitive engagement (CRT-2, Need for Cognition and Actively Open-Minded Thinking).Results : In Study 1, propensity to engage in reflective thought (higher CRT scores) was not significantly associated with activated mood or extreme appraisals, but activated mood and extreme appraisals were positively correlated. In study 2, the association between activation and extreme appraisals was replicated. Predicted associations between alternative measures of reflective thinking, activated mood, and extreme appraisals were not found.Conclusions : Extreme appraisals of internal states may be a psychological mechanism underlying activated mood. Propensity to reflect on and override default cognitions was unrelated to these extreme appraisals and activated mood. Further research in a clinical sample using mood-relevant measures of reflective thinking is warranted.